1987
DOI: 10.1029/jd092id04p04163
|View full text |Cite
|
Sign up to set email alerts
|

Mass accommodation coefficient for HO2 radicals on aqueous particles

Abstract: The rate of reaction of gas phase HO2 radicals with a monodisperse, submicrometer aerosol was measured in a flow tube reactor at atmospheric pressure. At the relative humidity of the experiments (75%), the aerosol consisted of concentrated solution droplets of either LiNO3 or NH4HSO4. When the aerosol contained a sufficient amount of Cu(II) ions, reaction of HO2 with the aerosol was observed. The mass accommodation coefficient for HO2 on aqueous particles was determined to be greater than 0.2. This implies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
140
2
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(156 citation statements)
references
References 40 publications
13
140
2
1
Order By: Relevance
“…Mozurkewich et al 23 observed highly efficient uptake of HO 2 onto Cu(II)-doped aerosols with  HO2 >0.2 (the value depending on the Cu(II) molality), which has been confirmed in recent studies 25,26 .…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Mozurkewich et al 23 observed highly efficient uptake of HO 2 onto Cu(II)-doped aerosols with  HO2 >0.2 (the value depending on the Cu(II) molality), which has been confirmed in recent studies 25,26 .…”
Section: Introductionsupporting
confidence: 51%
“…However, HO 2 uptake coefficients as determined by previous laboratory studies at room temperature are inconsistent and span a wide range of values. Measured HO 2 reactive uptake coefficients reported in the literature are summarized in Table 1 23 conducted the first laboratory measurements of HO 2 uptake onto aqueous aerosol particles doped with Cu(II) ions to catalyze the oxidation of HO 2 , and hence its removal in the bulk phase. These studies enabled the determination of the mass accommodation coefficient (), or the probability that a collision of a gas molecule with the aerosol surface leads to its incorporation into the aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…where Kn is the Knudsen number defined by where D g is the gas phase diffusion constant of HO 2 (0.25 cm 2 s −1 ) at room temperature (Mozurkewich et al, 1987). The Brown correction (Brown, 1978) was then applied to the uptake coefficients, in order to take into account the laminar flow in the flow tube.…”
Section: Discussionmentioning
confidence: 99%
“…The impact on HO 2 concentrations due to uptake onto these particles is unknown due to a lack of laboratory data. Sea-salt aerosols could also contribute significantly to the difference between the models and observations, especially if they contain small amounts of transition metal ions (Fitzsimmons et al, 2013), such as copper, which has been shown in laboratory studies to increase the HO 2 uptake coefficient significantly (George et al, 2013;Mozurkewich et al, 1987;Taketani et al, 2008;Thornton and Abbatt, 2005). Uptake coefficients of N 2 O 5 to illite aerosols (γ = 0.04-0.09, dependent upon RH), which is one of the most abundant clay minerals in dust, were measured to be considerably larger than for uptake to ATD (γ ∼ 0.006, weak if any dependence upon RH) (Tang et al, 2014).…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…In the measurements of the sticking coefficients of SO 2 (Gardner et al, 1987) and HO 2 (Mozurkewich et al, 1987) onto aqueous solutions, it has been found that the corresponding values of α i are slightly larger than 0.01. Wang and Crutzen (1995) indicated that under typical natural atmospheric conditions the uptake of trace gases into cloud or rain droplets depends only weakly on the values of sticking coefficient because of the limitations on diffusive transfer.…”
Section: Model Descriptionmentioning
confidence: 99%